Pedagogical Approaches to Boosting Reading Proficiency through Techniques and Strategies - Haryadi, Rofiq Noorman; Retnaningsih, Woro; Sujito, Sujito (Pasundan Social Science Development, 2025)
Improving reading proficiency in students requires effective pedagogical approaches that are tailored to the individual needs and learning styles. This article aims to explore various pedagogical techniques and strategies that can be employed to enhance reading skills. This research uses a literature review method to analyze different approaches that have proven effective in reading instruction. Techniques such as reading modeling, group discussions, and the integration of technology in reading instruction are evaluated based on evidence from previous studies. Additionally, methods such as strategy-based learning, direct instruction, and active reading comprehension techniques are analyzed to identify ways to improve text understanding and student engagement. Other methods explored include digital literacy-based learning, which utilizes technology platforms to enrich students' reading experiences. The findings suggest that using a combination of these techniques, tailored to the characteristics and needs of the students, can result in significant improvements in reading proficiency. The study also emphasizes the importance of ongoing assessment to adjust pedagogical approaches in alignment with the students' reading development